Decolonizing Gender Dynamics: Reclaiming Lawino’s Voice in Okot p’Bitek’s Song of Lawino - Mahuze, Yolenta Oktovia; Dewi, Novita (Indonesian Journal of English Language Studies (IJELS), 2024)
Using Ngũgĩ wa Thiong’o’s decolonization theory, this article argues that Okot p’Bitek’s Song of Lawino reclaims African cultural voice and identity. Even though it is available in English, Song of Lawino is a kind of narrative poetry borrowed from the traditional Acholi song. This study uses contextual and stylistic analysis to show how p’Bitek’s poetry acts as a force for decolonization, advocates for cultural preservation, and addresses collective issues. Findings show that by satirizing African middle-class elites who adhere to Western values, the two chapters from Song of Lawino studied “The Woman with Whom I Share My Husband” and “Let Them Prepare the Malakwang Dish” highlight the clash between European and African cultures. In these poems, Lawino challenges gender dynamics and defends traditional practices, as well as criticizes the shallowness of Westernized lifestyles adopted by her husband Ocol. Through this strong-willed woman’s criticism, Okot p’Bitek’s poetry reveals the negative impacts of credulous cultural assimilation and underlines the import